Pengaruh Struktur Utang dan Likuiditas terhadap Kinerja Perusahaan: Studi Empiris pada Perusahaan Farmasi yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2024 - Ichsan, Muhammad; Pebriyani, Dewi (Jurnal Eksplorasi Akuntansi, 2025)
This research is motivated by the pharmaceutical companies that are in high debt and have been sued, and company losses have increased sharply from the previous year. This study aims to examine the influence of debt structure and liquidity on firm performance among pharmaceutical companies listed on the Indonesia Stock Exchange from 2019 to 2024. This research utilized secondary data from financial statements of individual pharmaceutical companies obtained from the official website of the Indonesia Stock Exchange and respective company websites. The sample consists of 53 observations, employing multiple linear regression analysis with financial ratio analysis using IBM SPSS software. The results demonstrate that both debt structure and liquidity simultaneously have a significant influence on firm performance. The findings indicate that debt structure has a negative partial effect on firm performance, while liquidity has a positive partial effect on firm performance. Future research is recommended to explore additional internal and external variables and implement more dynamic analytical methods to better explain variations in firm performance.